Political Participation and Social Environment in Lithuania - Imrasaitė, Jūratė (Sociologija. Mintis ir veiksmas, 2002)
Modern democratic polity is essentially grounded on participation of citizens in public decision making process. The focus of this study was the impact of social environment on political participation. The method of study was survey sample data analysis. The results of analysis reflect relationship between number of people whom respondent discuss about political and societal matters and political participation. Data analysis confirms an assumption that social environment has an impact on political behaviour, i.e. in some cases social environment could encourage low status group political participation or discourage high status group political participation.
Keywords: political participation; social environment; interpersonal relationships; social structure; social communication